Levofloxacin induced bullous fixed drug eruption: a rare case report. (18th December 2020) - Sharma, Amit; Baldi, Ashish; Sharma, Dinesh Kumar
Abstract : A 42-year-old male patient visited the outpatient department for follow-up with a history of respiratory tract infection and diabetes mellitus. His main symptom was peeling of his epidermal layer of skin, and bullous fixed drug eruption on the lower and upper limbs and bank region of the body. Following assessment, the patient was prescribed levothyroxine, hydroxychloroquine, levofloxacin, and a combination of sulfamethoxazole-trimethoprim. On assessing causality of the adverse drug reaction (ADR), different ADR assessment scales such as the WHO-UMC Scale, Naranjo Scale, and Hartwig's Severity Assessment Scale were used, and the ADR was found by these scales to be 'likely', 'moderate', and 'probable', respectively. It was found that ADRs such as bullous fixed drug eruptions are not fatal but can cause patient anxiety and a reduced quality of life. This case report will help physicians and clinicians to become aware and vigilant about the ADR caused by levofloxacin, facilitating its early detection and management.